Food Neophobia in Wild Rats (Rattus norvegicus) Inhabiting a Changeable Environment—A Field Study - Modlinska, Klaudia; Stryjek, Rafał (PLOS ONE, 2016)
Food neophobia is a reaction to novel food observed in many animal species, particularly omnivores, including Rattus norvegicus. A neophobic reaction is typically characterised by avoidance of novel food and the necessity to assess both its potential value and toxicity by the animal. It has been hypothesised that this reaction is not observed in rats inhabiting a changeable environment with a high level of variability with regard to food and food sources. This study was conducted in such changeable conditions and it aims to demonstrate the behaviour of wild rats R. norvegicus in their natural habitat. The rats were studied in a farm setting, and the experimental arena was demarcated by a specially constructed pen which was freely accessible to the rats. At regular intervals, the rats were given new flavour- and smell-altered foods, while their behaviour was video-recorded. The results obtained in the study seem to confirm the hypothesis that rats inhabiting a highly changeable environment do not exhibit food neophobia. The observed reaction to novel food may be connected with a reaction to a novel object to a larger extent than to food neophobia. The value of the results obtained lies primarily in the fact that the study was conducted in the animals’ natural habitat, and that it investigated their spontaneous behaviours.